The Historical Jesus and Human Subjectivity: A Response to John Meier - Kelly, Anthony (Pacifica, 1991)
Problems associated with the distinction between the historical Jesus and the historic Jesus can be satisfactorily clarified only by paying much greater critical attention to the subject, the person making and using such distinctions, and by a methodological reintegration of the wholeness of consciousness. Faith can thus employ historical scholarship, not cowed or threatened, but astutely aware of the possibilities, limitations and necessity of searching into its past, and of incarnating itself in this stream of time, space, human experience and development.